PEMBERDAYAAN IBU RUMAH TANGGA DALAM PEMANFAATAN MICROGREEN DAN HEALTHY JUICE UNTUK GIZI KELUARGA - Mairawita; Zozy Aneloi Noli; Feskaharny Alamsjah; Solfiyeni; Mildawati (Universitas Nusa Bangsa, 2024)
Microgreens and healthy juice are closely related to family nutrition and a healthy lifestyle. This community service activity aims to empower homemakers to use microgreen vegetables in the form of kale and kale and make healthy juice from these vegetables to fulfill family nutrition needs as part of efforts to live a healthy lifestyle. Community service activities regarding the introduction of microgreens and healthy juices were held on June 13, 2024, in Limau Manis Selatan Village, Unand Block B lecturer housing complex, Ulugadut, Pauh District, Padang, which was attended by 50 members of Majlis Taklim Darul Ulum. Implementation methods include socialization, discussion, and direct practice. As many as 90% of participants showed increased knowledge about microgreens, and 85% better understood the importance of healthy juice and how to make it. Awareness regarding participants' nutritional knowledge increased, with greater interest in including microgreens and healthy juices in their daily diet. Activities achieved satisfactory results as demonstrated by high participation and enthusiasm during socialization, discussion, and practice sessions. At the end of the activity, interviews were conducted with participants. Live demonstrations and independent practice are proven effective in teaching new knowledge and skills. Challenges such as time and material limitations were overcome with a follow-up plan, including forming small working groups and follow-up sessions to evaluate progress. This activity increased the knowledge, skills, and enthusiasm of Majlis Taklim Darul Ulum members to live a healthy lifestyle. Post-training, the results show the potential for sustainability in encouraging healthy lifestyles of training participants and strengthening communities.